An Overview on Cancer treatment and therapy (International Journal of Innovative Research in Computer Science & Technology, 2022)
Cancer is indeed a group of illnesses, and  each has its own range of symptoms, and each organ and  system has its own list of conditions. Many cases of breast  cancer may well be averted, with some estimates claiming  that up to 30% of cancer deaths are connected to smoking  and other lifestyle choices or food habits that could have  been avoided by behavioral changes. Cancer therapy is a  treatment of tumor in a patients through surgery,  chemotherapy, or irradiation. Targeted therapies are also  available for specific cancer types. A cancer sufferer may  be subjected to a range of therapies, including those  targeted at reducing cancer pain sensations.  Nanotechnology has the ability to improve the selectivity  or efficacy of physical, chemical, or biological methods to  cancer cell killing while reducing nonmalignant cell  damage. Nanomaterials are progressively being used to  target tumor cells with high selectivity, both actively or  passively. The primary goal of this study is to have a better  understanding of cancer treatment and therapy.
Keywords: Cancer Treatment; chemotherapy Nanotechnology; Radiation; Surgery